DEVELOPING BEGINNING READING USING PICTURE AND PICTURE LEARNING MODEL - Siti Khasinah; Yuni Setia Ningsih (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2023)
The reading ability of beginner students at SD Negeri Lamklat is still low. In a reading lesson, they can name the letters of the alphabet in the reading sequence from A to Z. However, if the letters are scrambled, most students cannot remember how to pronounce the letters correctly. Apart from that, their pronunciation and intonation when reading are also inappropriate. Therefore, this research aims to determine the influence of the Picture and Picture learning model to improve the beginning reading skills of grade I students at SD Negeri Lamklat, Kabupaten Aceh Besar. The research method used is the One Group Pre-test-Post-test Design of Pre-Experiment. The sample of this study was 22 grade 1 students. An oral pre-test and post-test were used to collect the data. Completion of the initial reading ability test results is carried out using statistical tests with a significance level of 0.05 and using the percentage formula. The results of the research show that the use of pictures and pictures influences the students' ability. After testing, it is found that t-test = 4.395 and t-table = 1.721. Thus, t-test ≥ t-table or 4.395 > 1.721. Therefore, it can be concluded that the hypothesis in this research (Ha) is accepted. In addition, the average score for the pre-test was 51.363 and the post-test was 91.363. Thus, the finding shows that there is an impact of the use of the Picture and Picture learning model in developing the initial reading ability of the students.